The relationship between fat talk and body image in Chinese female nursing students: The mediating role of self-acceptance - Fengxia Wang; Yuxiao Wang; Yufan Wang; Qihao Yang; Ju Qiu; Jinyan Li; Meng Liu; Xiaowei Wang; Li Li; Xichao Xia (PLoS ONE, 2026)
Objective This study examined whether self-acceptance mediates the relationship between fat talk and body image among Chinese female nursing students, a group under high appearance pressure. Methods A cross-sectional survey was conducted among 1,280 female nursing students from five medical universities in Henan Province, China, Participants were recruited from randomly selected classes, and questionnaires were distributed in person via QR codes.. Participants completed validated scales measuring fat talk (Fat Talk Scale), self-acceptance (Self-Acceptance Questionnaire), and body image (Body Image States Scale). Data were analyzed using correlation and mediation analysis (PROCESS macro, Model 4) with bootstrapping. Results Fat talk was positively correlated with both self-acceptance (r = 0.543, p < 0.001) and body image (r = 0.344, p < 0.001). Self-acceptance was also positively correlated with body image (r = 0.457, p < 0.001). After controlling for “relationship status, grade, only child status, and BMI,Mediation analysis revealed a significant indirect effect of fat talk on body image through self-acceptance (effect = 0.174, 95% CI [0.132, 0.222]), accounting for 57.80% of the total effect (total effect = 0.301). The direct effect remained significant (effect = 0.127, 95% CI [0.032, 0.222]).The standardized indirect effect (β = 0.080) indicates a small-to-moderate effect size. Conclusion Among Chinese female nursing students, engaging in fat talk conversations is associated with a more positive body image. Self-acceptance accounting for 57.80% of the total effect, though the standardized indirect effect (β = 0.080) suggests a small-to-moderate effect size. This finding highlights the importance of cultural and contextual factors in shaping body discourse and suggests that fostering supportive communication environments and self-acceptance could be beneficial in this population.